A Brief Review of the Role of Lifestyle Factors in the Relationship Between Urban Air Pollution and Mental Wellbeing from an Evolutionary Viewpoint - O, Jiaqing; Liang, Jiahao (Current pollution reports, 2025)
Purpose of Review Outdoor air pollution, the scourge of modern urban living, has long been associated with an array of adverse health outcomes. While empirically supported strategies have already been prescribed for individuals to effectively lessen the impact of contaminated air on their physical health, much is still unknown about comparable solutions for mental wellbeing. The utility of an all-embracing framework that could offer a parsimonious elucidation of existing apparently-heterogeneous work is contended to be pivotal, and this narrative review will address this by reviewing recent main findings through the lens of evolutionary mismatch theory. Recent Findings In general, recent evidence suggests that the evolutionary mismatch theorisation (which posits that air pollution–induced lifestyle changes could play an influential role in modifying mental wellbeing outcomes due to their evolutionarily unfamiliar nature) might be valid. More specifically, the air pollution–mental wellbeing link (tentatively) appears to have been influenced by (1) the evolutionarily mismatched curtailment of physical activities, (2) sunlight exposure, and (3) social contact, together with (4) the evolutionarily mismatched overexposure to upsetting information. The jury is still out for the proposed role of the evolutionarily mismatched reduction of greenery exposure, while the very limited evidence does not support the postulated influence of evolutionarily mismatched opportunities for comparisons with others via media. Summary Findings from this review (tentatively) propound that deleterious mental-wellbeing consequences due to urban air pollution could be mitigated if individuals maintain a more evolutionarily familiar lifestyle within the limits of their circumstances. Graphical Abstract